Liberalism without perfection - Quong, Jonathan, 1977- (Oxford : Oxford University Press, 2011)
'Liberalism Without Perfection' offers an introduction to the debate between liberal perfectionism and political liberalism. This book is an account and defence of Rawlsian political liberalism, one of the most discussed, but widely misunderstood and criticized theories in contemporary political theory.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Liberalism; Liberalism -- Philosophy; Rawls, John, -- 1921-2002.